Karakterisasi parameter model prediksi untuk eleviasi dari perangkap kemiskinan melalui intervensi kebijakan fiskal - Agus Setiawan; S Bakri; A Effendi; I Nurhaida (Faculty of Social and Political Science, Universitas Airlangga, 2014)
The purpose of this study was to develop a model of poverty eleviation in the buffer zone of National Park through the optimization of the impact of the fuel subsidiary reallocation (BLT), statrted from April to October 2013 in three villages which representent ethnic culture in Lampung, Java, and the mixture of both, selecting 50 poor households (RTM) who received BLT (direct cash assistance) in 2005. In-depth interview was conducted to capture the economy performance of each household. Qualitative probability model was applied to the response variable (Yi) that were scored 1 for those have been exited from the poverty and scored 0 if not yet. The predictor variables used (Xij) including: fuel prices (Rp/liter), total of BLT (Rp), demographics (age, sex, family head education, as well as the number of dependents), the value of productive assets (Rp million/household), revenue from damar resin, and other sources (Rp million/household), access to public services, the distance to the border of BBSNP, the availlability of PNPM (national project of community empowermnent that scored 1 if any and 0 if not), the performance of social capital and the extention program conveyed. The Minitab Version 16 was employed for exzamining the goodness to the model and the significancy of the parameters pursued at the level of 5% and 10%. The conclusions were the exit capability against poverty were significantly affected by: fuel prices, the ammount of the BLT, the exisistency of PNPM, gender & education of household, number of dependents, the distance to central districts, the presence of electricity, the power of social capital, land ownership of both damar agroforest and paddy field acreages, the owner of productive assets such as ruminants. Accordingly, there were no culturetribe significantly affected by the existing from of poverty, which means that the poverty in this region was more structural cause than that of the cultural one.